Sustainable Practice of Ogoh-ogoh: An Ecological Perspective on Integrating Environmental Conservation with Cultural Heritage - Dewanto; Shanty Anugerah Yuni Puspita Sari Duwila; Olivia Jessi Febrianti (Universitas Negeri Medan, 2026)
The processes of crafting, parading, and burning the Ogoh-ogoh carry spiritual significance for Hindu communities in Indonesia. Despite its deep spiritual and philosophical meaning, the Ogoh-ogoh celebration is not without controversy. Environmental critics have raised concerns regarding the materials used in Ogoh-ogoh construction, including paints and dyes, as well as the environmental impact of the burning process. The objective of this study is to describe the cultural practices of Ogoh-ogoh in Surabaya and Gresik, particularly in relation to cultural preservation and environmental conservation. The research employs a Descriptive Qualitative Method. Content Analysis will be used to interpret the data. The research locations are Pura Perak in Surabaya and Kampung Bongso Wetan in Gresik. The subjects of this study include Hindu religious leaders, Ogoh-Ogoh artisans, and environmental enthusiast communities. Data were collected through literary studies, participatory observation, and in-depth interviews. The steps of data analysis are: 1) examining literature, policy documents, and archival materials, 2) conducting open coding, 3) categorizing codes, 4) applying selective coding, 5) interpreting data from observation and interview, 6) integrating data from cultural to ecological points of view, and 7) drawing conclusions. Findings reveal that local communities are actively integrating biodegradable and non-biodegradable materials to create Ogoh-ogoh. Styreofoam, plastic raffiah, and metal wires are continously used due to their affordability, accessibility, and malleability. This research offers a model for sustainable cultural practice that bridges tradition and innovation, emphasizing the role of community agency in shaping environmentally conscious heritage. It aims to inspire policy frameworks and educational initiatives.